Microbiota in swine wastewater treatment plant and area of Tifton 85 grass production - Sarto, Jaqueline Rocha Wobeto [UNESP]; Neres, Marcela Abbado; Sunahara, Samantha Mariana Monteiro; Nath, Caroline Daiane; Stangarlin, José Renato; Sarto, Marcos Vinicius Mansano [UNESP] (Universidade Estadual de Londrina, 2018)
The objective of this study was to evaluate the effects of biodigester treatment on the microbiological characteristics of swine wastewater (SW) at the production and storage sites, and to characterize and compare the microbiological composition of the soil, organic matter, and plants in the area of hay and haylage production. The area has been planted with Tifton 85 grass for eight years; and is exclusively intended for hay and haylage production, SW was used as the only fertilizer source. The experimental design was completely randomized with subdivided plotsin timeand five replications; the plots were the main areas of the SW in natura (affluent), the biodigester outlet (effluent), the storage pond, and the area of Tifton 85 production, which included the soil, plant residue on the soil surface (organic matter), and the aerial parts of the grasses with subplots in the rainy and dry seasons. The microbial count in the SW was reduced during the treatment process, with higher counts in the affluent, and lower counts in the effluent and storage pond. The SW treatment was ejficient in reducing the microbial population. The populations of Bacillus and Clostridium were influenced by the season of the year, with larger populations during the rainy season (summer) than during the dry season (winter). The mold genera identified in the SW area were Penicillium, Rhizopus, Fusarium, Helminthosporium, and Phoma. The genera Penicillium, Rhizopus, Fusarium, Cladosporium, Helminthosporium, Bipolaris, Phoma, Aspergillus, and Trichoderma were found in the area of Tifton 85 production.
Keywords: Forage; Manure; Microorganisms; Soil